Evaluation of breast carcinoma regression after preoperative chemotherapy by label‐free multiphoton imaging and image analysis. Issue 1 (18th October 2019) - Li, Lianhuang; Han, Zhonghua; Qiu, Lida; Kang, Deyong; Zhan, Zhenlin; Tu, Haohua; Chen, Jianxin
Abstract: Neoadjuvant chemotherapy is increasingly being used in breast carcinoma as it significantly improves the prognosis and consistently leads to an increased rate of breast preservation. How to accurately assess tumor response after treatment is a crucial factor for developing reasonable therapeutic strategy. In this study, we were in an attempt to monitor tumor response by multimodal multiphoton imaging including two‐photon excitation fluorescence and second‐harmonic generation imaging. We found that multiphoton imaging can identify different degrees of tumor response such as a slight, significant, or complete response and can detect morphological alteration associated with extracellular matrix during the progression of breast carcinoma following preoperative chemotherapy. Two quantitative optical biomarkers including tumor cellularity and collagen content were extracted based on automatic image analysis to help monitor changes in tumor and its microenvironment. Furthermore, tumor regression grade diagnosis was tried to evaluate by multiphoton microscopy. These results may offer a basic framework for using multiphoton microscopic imaging techniques as a helpful diagnostic tool for assessing breast carcinoma response after presurgical treatment. Abstract : Multimodal multiphoton imaging including two‐photon excitation fluorescence and second‐harmonic generation was used to identify different degrees of tumor response such as a slight, significant, or complete response and can detect morphological alteration associated with extracellular matrix during the progression of breast carcinoma following preoperative chemotherapy. These results may offer a basic framework for using multiphoton microscopy as a helpful diagnostic tool for assessing breast carcinoma response after neoadjuvant treatment.